(3OjhGf LQjQs - (3LQjQ Hf YWjI Hf MPjaI GdNWaj GdjQHhYj GdJejej,J (B110 (3g` s
(3ChdgG (B:s
(3bGd LQjQ jgLh GdCNWd(B: (3Mj GdZOGI HQGeI GdCWdGdG QSeG JMed Cgdg aCMGdG s
(3BNQgG (B:s
(3faSj GdaOGA dbhe RjfhG MSHj hEf eQVJ age Cgdj hYhGOj Ef JLQ WjQ HCeQ ajg YGajI Ch HGdaQGb abO CMSfJe fGOj gfG BNQ TYQ LQjQ Hf GdNWaj s
(3fSNI KGdKI Yf fSNI cJHgG YHOGddg Hf RjGO Hf SdjeGf SfI (B1194 (3g`s
(3hbO SbWJ hQbJj (B58(3,(B59 (3ef Gdajde s
(3hQO CjVkG JMJ Qbe (B831(3, (B832(3, (B877(3, (B1020(3, (B1021(3, (B1022(3, (B2399 s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs